The Strategy of School Heads As Managers inThe Era of The Industrial Revolution 4.0 - Wibowo, R. Satria; Ahyani, Nur; Widayatsih, Tri (Jurnal Pendidikan Tambusai, 2021)
This study aims to describe the principal's strategy as a manager in order to carry out four managerial functions in the era of the industrial revolution 4.0. The research method used in this research is qualitative. The research was conducted at SMA Negeri 1 Talang Ubi. Observation data collection techniques, interviews and documentation. The data analysis technique used by researchers is Miles and Huberman. The results show that the strategy of the Head of SMA Negeri 1 Talang Ubi in the planning function has been carried out through disciplinary enforcement with fingerprints, and preparation of learning infrastructure using digitization. The organizing function has been carried out well, through the preparation of students to continue to a higher level. the coordination function runs well by utilizing technology and information, so that most activities are carried out well. The monitoring function has been carried out with the use of technology, such as the use of a CCTV camera connected directly to the headphones and to the principal's room at SMA Negeri 1 Talang Ubi so the control is faster and more accurate.